Self-Regulation and Regulatory Teaching as Determinants of Academic Behavioral Confidence and Procrastination in Undergraduate Students - de la Fuente, Jesús; Sander, Paul; Garzón-Umerenkova, Angélica; Vera-Martínez, Manuel Mariano; Fadda, Salvatore; Gaetha, Martha Leticia (Frontiers in psychology, 2021)
The combination of student Self-Regulation (SR) and the context of Regulatory Teaching (RT), each in varying degree, has recently been demonstrated to have effects on achievement emotions, factors and symptoms of stress, and coping strategies. The aim of the present research study is to verify its possible further effects, on academic behavioral confidence and procrastination. A total of 1193 university students completed validated online questionnaires with regard to specific subjects in their degree program. Using an ex post facto design, multivariate analyses and structural equation modeling (SEM) were carried out in order to test the relationships predicted by the model. SR and RT had a significant joint effect in determining the degree of academic behavioral confidence and of procrastination. Academic behavioral confidence also significantly predicted reasons for procrastinating, and these in turn predicted activities of procrastination. Conclusions are discussed, insisting on the combined weight of the two variables in determining academic behavioral confidence, reasons for procrastinating and activities subject to procrastination, in university students. Implications for guidance and educational support of university students and teachers are analyzed.